Predictors of Delayed Wound Healing after Endovascular Therapy of Isolated Infrapopliteal Lesions Underlying Critical Limb Ischemia in Patients with High Prevalence of Diabetes Mellitus and Hemodialysis. Issue 5 (May 2015) - Shiraki, T.; Iida, O.; Takahara, M.; Soga, Y.; Yamauchi, Y.; Hirano, K.; Kawasaki, D.; Fujihara, M.; Utsunomiya, M.; Tazaki, J.; Yamaoka, T.; Shintani, Y.; et al.
<x xml:space="preserve">Abstract</x> Objectives Acceptable limb salvage rates underlie the widespread use of endovascular therapy (EVT) for patients with critical limb ischemia (CLI) secondary to isolated infrapopliteal lesions; however, post-EVT delayed wound healing remains a challenge. Predictors of delayed wound healing and their use in risk stratification of EVT in patients with CLI due to isolated infrapopliteal lesions are explored. Methods This was a retrospective multicenter study. 871 consecutive critically ischemic limbs were studied. There was tissue loss in 734 patients (age: 71 ± 10 years old; 71% male) who had undergone EVT between April 2004 and December 2012. The wound healing rate after EVT was estimated by the Kaplan–Meier method. The association between baseline characteristics and delayed wound healing was assessed by the Cox proportional hazard model. Results Diabetes mellitus and regular dialysis were present in 75% (553/734) and 64% (476/734) of patients, respectively; 67% of limbs (585/871) had Rutherford class 5 CLI; 8% (67/871) of wounds were located in the heel only; 25% (219/871) of limbs had Rutherford 6 (involving not only the heel); and 42% (354/871) of wounds were complicated by infection. The rate of freedom from major amputation at 1 year reached 88%, whereas the wound healing rate was 67%. Median time to wound healing was 146 days. By multivariate analysis, non-ambulatory status (hazard ratio [HR], 1.58; 95% confidence interval [CI] 1.31–1.91) serum albumin <3 g/dL (HR 1.42; 95% CI 1.08–1.86), Rutherford 6 (not only heel) (HR 1.68; 95% CI 1.33–2.14), wound infection (HR 1.24; 95% CI 1.03–1.50), EVT not based on angiosome concept (HR 1.28; 95% CI 1.06–1.55), and below the ankle (BTA) 0 vessel runoff after EVT (HR 1.45; 95% CI 1.14–1.86) were independent predictors of delayed wound healing. Conclusions Non-ambulatory status, low albumin level, Rutherford 6 (not only heel), wound infection, indirect intervention, and poor BTA runoff were independent predictors for delayed wound healing after EVT in patients with CLI secondary to infrapopliteal lesions, and their use in risk stratification allows estimation of the wound healing rate.